Inspiracje teoretyczne konkurencyjności według Thünena, Marshalla, Portera - Mazurkiewicz-Pizło, Anna; Pizło, Wojciech (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
In the article is presented selected theoretical aspects of competitiveness according to classical economists: Johann von Thünen, Alfred Marshall and Michael Porter. There is the theoretical clusters conception particularly cluster initiatives and conditions of their developments.